Adapting a dyadic exercise program to be culturally relevant for Hispanic men with prostate cancer using community engagement studio: a brief report - Skiba, Meghan B.; Badger, Terry A.; Garcia, David O.; Chilton, Floyd H.; Winters-Stone, Kerri M. (Frontiers in Psychology, 2024)
Background: Cancer disparities exist for Hispanic men with prostate cancer and their caregivers that could be lessened with exercise. Exercising Together© is a six-month evidenced-based dyadic resistance training program that promotes teamwork between prostate cancer survivors and their spouses to improve physical, mental, and relational health outcomes. The purpose of this study was to elicit feedback and recommendations from stakeholders on the Exercising Together© intervention to inform the cultural adaptation of this program for Hispanic men with prostate cancer.We conducted a virtual Community Engagement Studio (V-CES) with community expert stakeholders representative of the Hispanic and cancer care community in Southern Arizona. The V-CES process included orientation, presentation of research, guided discussion, and evaluation. The V-CES was audio recorded, transcribed, and rapidly analyzed to identify actionable feedback and contextual adaptions.Results: Nine stakeholders (6/9 male; 5/9 Hispanic) completed all V-CES activities. Through stakeholder engagement and feedback from the V-CES, adaptations to the original Exercising Together© intervention include: 1) inclusion of the cancer survivor identified caregiver that might not be a spouse; 2) availability in English and Spanish; 3) shortening the intervention to threemonths; 4) remote delivery of the intervention; and 5) incorporation of low burden procedures. Conclusions: Findings from our V-CES informed the adaptations for a culturally relevant dyadic progressive resistance training program for Hispanic men with prostate cancer and their caregivers.